SOSIALISASI MODEL PEMBELAJARAN INOVATIF BAGI MAHASISWA STKIP PGRI LUBUKLINGGAU - Juwati Juwati; Satinem Satinem; Agung Nugroho (LP4MK STKIP PGRI Lubuklinggau, 2021)
Community service activities aim to disseminate creative and innovative learning models for STKIP PGRI Lubuklinggau students. This socialization activity was carried out by the dedication team to develop the knowledge of students who had taken course learning models, microteaching as a provision for field practice or PPL. Participants in this activity were students from STKIP-PGRI Lubuklinggau as many as approximately 150 students. The results of the socialization obtained that students were very enthusiastic and related to the program delivered by the Service Team. This can be seen during the question and answer session, students are interested in asking questions about the steps of creative and innovative learning models as a provision for implementation in the field.